2016
DOI: 10.1111/bju.13443
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and timing of venous thromboembolism after radical cystectomy in routine clinical practice: a population‐based study

Abstract: Over half of VTE events in RC patients occur after hospital discharge, with a substantial incidence up to 3 months after surgery. Limited actionable risk factors for VTE were identified other than LOS. In this population-based cohort, VTE was associated with inferior long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Several studies have shown that a large proportion (45%–55%) of VTEs occur after discharge from hospital, [6, 14] including our previous work, [13]; this observation lends support to the role of extended thromboprophylaxis. In the present study, we found that 61% of VTE events occur after discharge.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several studies have shown that a large proportion (45%–55%) of VTEs occur after discharge from hospital, [6, 14] including our previous work, [13]; this observation lends support to the role of extended thromboprophylaxis. In the present study, we found that 61% of VTE events occur after discharge.…”
Section: Discussionsupporting
confidence: 80%
“…Fifty-eight percent of events occurred before RC. Our previous work did not identify an association between delivery of adjuvant chemotherapy (ACT) and VTE [13]. A systematic review and meta-analysis of 5082 of patients with bladder cancer treated with chemotherapy for any stage of disease describe an overall VTE rate of 7% [17].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, patients undergoing major cancer surgery have a significant risk of postoperative VTE, with evidence showing that rates of VTE are increasing over time . Although guidelines for VTE prophylaxis are not uniform, this study's findings that most VTEs occur after discharge is a reason for urological surgeons to strongly consider extended VTE prophylaxis in this high‐risk population.…”
mentioning
confidence: 80%
“…Using a large comprehensive population‐based cohort from Canada, Doiron et al. present an in‐depth analysis of risk factors and timing of venous thromboembolism (VTE) after radical cystectomy (RC) for bladder cancer. This report reiterates what is already known, which is that VTE after RC occurs at a non‐negligible rate (5.4%) and most VTEs occur after hospital discharge (55%).…”
mentioning
confidence: 99%
See 1 more Smart Citation